2020
DOI: 10.7249/rr4394
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide Evaluation of Health Care Prices Paid by Private Health Plans: Findings from Round 3 of an Employer-Led Transparency Initiative

Abstract: The largest source of health insurance coverage in the United States is through an employer or union. Despite the size and importance of this market, prices are opaque. In this study, we use 2016 to 2018 data from all but one state in the United States, covering $33.8 billion in hospital spending from three sources-self-insured employers, state-based all-payer claims databases, and health plans-to document variation in facility and professional prices for the commercially insured population. We also examine tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(54 citation statements)
references
References 47 publications
4
50
0
Order By: Relevance
“…of Medicare payments for the same services in 2018. 27 While this is not delineated for speci c medications, it suggests a potential benchmark for elevated cost expectations beyond that calculated in our analysis. Use of the trial limited our analysis to a single medication, so there is no comparison to the costs and clinical or radiologic bene t of alternative systemic agents.…”
Section: Discussionmentioning
confidence: 80%
“…of Medicare payments for the same services in 2018. 27 While this is not delineated for speci c medications, it suggests a potential benchmark for elevated cost expectations beyond that calculated in our analysis. Use of the trial limited our analysis to a single medication, so there is no comparison to the costs and clinical or radiologic bene t of alternative systemic agents.…”
Section: Discussionmentioning
confidence: 80%
“…The literature on consolidation in the hospital industry has shown that when health systems merge, their market power increases and they are able to leverage this into higher reimbursement rates with private insurers. 28 , 29 In contrast, when dialysis facilities merge, their negotiating power increases only modestly because the majority of patients with ESKD are covered by traditional Medicare. 30 However, LDOs can use a number of other strategies to increase their revenue.…”
Section: Discussionmentioning
confidence: 99%
“…26 A recent report found that payments to both UPMC and AHN system-affiliated hospitals are also below national averages. 27 Long-term viability. Interviewees believed that consolidation was mostly beneficial for the long-term viability of Pittsburgh's health care institutions.…”
Section: (Continued)mentioning
confidence: 99%